Chlamydia Infection as a Risk Factor for Cervical Cancer: A Systematic Review and Meta-Analysis - Anaanthan Bhuvanendran Pillai; Chin Mun Wong; Noor Dalila Inche Zainal Abidin; Sharifah Fazlinda Syed Nor; Mohd Fathulzhafran Mohd Hanan; Siti Rasidah Abd Ghani; Nurul Afzan Aminuddin; Nazarudin Safian (Tehran University of Medical Sciences, 2022)
Background: We reviewed studies on the prevalence of Chlamydia infection as a risk factor for developing cervical cancer in a meta-analysis studies published in that subject area. Methods: Cochrane Library and PubMed databases were systematically searched for articles (observational and randomized controlled trials) published from 2008-2018. A meta-analysis of studies was performed to analyse the association between chlamydia infection and cervical cancer. Results: Five articles were included in the final analysis (N=5271). All five articles were case-control studies, of which three studies sampled from population-based registries. All studies involved with sexually active women with minimum 15 years old. Three studies reported the association of C. trachomatis infection cervical cancers, two other studies reported C. trachomatis-HPV co-infection in association with cervical cancer. Result showed C. trachomatis has an overall prevalence of 31.9%, pooled OR 1.96, 95% CI 1.05 to 3.67, OR 2.13, 95% CI 1.78 to 2.54 among cervical cancer. There was a mild publication bias detected at 3.0 effect estimation. Heterogeneity detected from clinical and methodological diversities particularly from C. trachomatis-HPV co-infection subgroup analysis, including sampling bias, geographical strain diversity, and different outcome endpoint measured. Conclusion: C. trachomatis infection was significantly associated with the development of cervical cancer. Co-infection of C. trachomatis-HPV with cervical cancer is plausibly sound but temporality of C. trachomatis-HPV with the development of cervical cancer need to be proven in future prospective cohort studies.